Broadcast news - Brooks, James L. 1940-; Hurt, William 1950-2022 (The Criterion collection, 2010)
A caustic inside look at the Washington news media, stars Holly Hunter in her breakout role, as a feisty television producer torn between an ambitious yet dim anchorman and her closest confidant, a cynical veteran reporter. James L. Brooks' witty, gently prophetic entertainment is a captivating transmission from an era in which ideas on love and media were rapidly changing